Spin-texture-driven electrical transport in multi-Q antiferromagnets - Soonbeom Seo (Communications Physics, 2021)
The magnetic, electronic, and structural properties of a quantum material are intrinsically linked. In f-electron systems, such as cerium-based materials, this interplay can be exceedingly complex. Here, the authors investigate the antiferromagnet CeAuSb2 using a Kondo lattice model in order to resolve the changes in conductance that occur with variations in the magnetic spin texture as function of applied magnetic field.